UPAYA PENCAPAIAN IKLIM USAHA KONDUSIF BAGI PENANAMAN MODAL (INVESTASI) DALAM KEGIATAN BISNIS PARIWISATA - Kezia Frederika Wasiyono; I Ketut Sudiarta (Kertha Negara : Journal Ilmu Hukum, 2013)
Indonesia as one of the countries that have the greatest investment in the world, one in the tourism business activities. Investment tourism business nowadays are experiencing adversity, therefore it is necessary to fix all variety of contributing factors that hinder investment climate and policy making that can provide security, legal certainty and legal protection for investors. So by making such efforts, the conducive business climate can be achieved and not difficult to make Indonesia as the country's state investment objectives in the field of tourism as well as in many other fields. In this journal, use of normative legal research methods.